PET Visualized Stimulation of the Vestibular Organ in Menière's Disease - Devantier, Louise; Hansen, Allan K.; Mølby-Henriksen, Jens-Jacob; Christensen, Christian Bech; Lildal, Tina; Pedersen, Michael; Magnusson, Måns; Borghammer, Per; Ovesen, Therese (Frontiers in Neurology, 2020)
Introduction: The cortical metabolic activity in patients with Menière’s disease has not been investigated. The aim of this study was to investigate the 18F-FDG cerebral uptake in Menière’s patients compared to healthy controls. Method: Eight patients with right-sided Menière’s disease and fourteen healthy controls underwent a video head impulse test (vHIT), test of utricular function with ocular vestibular evoked myogenic potentials (oVEMP) and three 18F-FDG-based PET examinations of the brain. Participants were seated in a self-propelled chair, injected with 18F-FDG and then exposed to 35 min of chair motion stimulation, followed by a PET scan. Two types of natural vestibular stimuli were applied, predominantly towards the right horizontal semicircular canal (angular acceleration) and right utriculus (linear acceleration). For baseline scans, participants were injected with 18F-FDG while seated without movement. Results: Analyses of baseline scans revealed decreased 18F-FDG-uptake in the medial part of Heschl’s gyrus in the left hemisphere in patients with Menière’s disease compared to healthy controls. During angular vestibular stimulation there was also a significantly decreased 18F-FDG uptake in the intersection between the medial part of Heschl’s gyrus and the parietal operculum in the left hemisphere and bilaterally in the posterior part of insula. During linear stimulation, Menière’s patients showed decreased 18F-FDG uptake in the medial part of Heschl’s gyrus in the right hemisphere and also bilaterally in the posterior insula. In addition, decreased 18F-FDG uptake was seen in the thalamus during vestibular stimulation. Conclusion: Heschl’s gyrus, the posterior part of insula, and thalamus have previously been shown to be core areas for processing vestibular inputs. Patients with Menière’s disease solely differed from the healthy controls with lower cortical activity in these areas at baseline and during natural vestibular stimulation.